Oral tolerogenic vaccine combined with gastrin restores immune tolerance and beta-cell function in NOD mice with Type 1 diabetes - Cobb, Jacob; Rawson, Jeffrey; Gonzalez, Nelson; Kandeel, Fouad; Husseiny, Mohamed I. (Frontiers in Immunology, 2026)
Background and objectiveType 1 diabetes (T1D) results from autoimmune destruction of pancreatic β-cells. Current therapies fail to address the multiple mechanisms driving disease progression. We developed an oral Salmonella-based vaccine that partially prevented and reversed autoimmune diabetes in mice. Gastrin, an intestinal hormone, has been reported to have anti-inflammatory and β-cell-protective effects. We hypothesized that combining the vaccine with a gastrin analogue (GAST-17) could enhance therapeutic efficacy.MethodsFemale non-obese diabetic (NOD) mice were treated with the oral vaccine, GAST-17, or their combination. Blood glucose levels, islet histology, immune cell infiltration, cytokine profiles, and regulatory T cell populations were assessed. Functional assays included antigen-specific stimulation, adoptive transfer, and analysis of immunoregulatory gene expression.ResultsCombination therapy demonstrated superior efficacy in both diabetes reversal and prevention. In reversal studies, diabetes remission was achieved in 80% of mice receiving the combination therapy, compared with 63% in the vaccine-only group and 5% in the GAST-17-only group. In prevention studies, diabetes onset was prevented in 80% of mice receiving the combination therapy, compared with 70% in the vaccine-only group and 30% in the GAST-17-only group. Therapeutic effects were associated with increased antigen-specific regulatory T-cells, reduced islet-infiltrating lymphocytes, preserved insulin-positive islet area and β-cell mass, and modulation of cytokine profiles, including elevated IL-10 and TGF-β and reduced IFN-γ, GM-CSF, IL-1α, and IL-12. Upregulation of immune checkpoint molecules (CTLA-4 and PD-L1) and immunoregulatory mediators (AhR, IDO, and IL-27) was observed, suggesting a potential contribution to immune homeostasis.ConclusionsThe combination of the oral Salmonella-based vaccine and GAST-17 improved glycemic control in NOD mice and was strongly associated with β-cell preservation and immune regulation. This dual-acting strategy, integrating immune modulation with β-cell preservation, may offer durable therapy in autoimmune diabetes and could have potential for future clinical translation.